Patient Satisfaction in the Treatment of Acute Hamstring Strain Injury - Ling, L.L.; M. Nahar, A.M.; Lim, B.H.; Hamid, M.S.A.; Khoo, S.; Yusof, A. (Australian International Academic Centre, 2014)
Introduction: The impact of musculoskeletal injuries often caused loss time in sport participation. Athletes who suffered from these injuries experienced a decrease in performance and physical disability. Although a variety of treatments have been implemented to the muscle injuries, the administration of autologous blood injection is replacing the conventional rehabilitation to expedite the process of muscle recovery. Platelet-rich plasma (PRP) is relatively new in muscle injury treatment and there is lack of evidence of the satisfaction of PRP treatment in muscle injuries. Purposes: The study aimed to investigate the patient satisfaction in the administration of PRP treatment and rehabilitation program for acute hamstring strain injury. Methods: Participants (competitive, semi-competitive and recreational athletes) with acute hamstring strain injury (Grade II) were recruited. Participants were randomly divided into either the PRP treatment or rehabilitation program. Participants were required to attend weekly follow up assessment for recovery evaluation. All the participants were required to complete a patient satisfaction questionnaire (PSQ-18) at the end of study. The questionnaire is divided into seven sub-scales: general satisfaction, technical quality, interpersonal manner, communication, financial aspect, time spent with doctor, accessibility and convenience. Results: Participants were 22.35 ± 3.41 years. Duration from injury to first presentation in clinic ranged from two to ten days. Mean duration of recovery was 5.64 weeks. No statistically significant difference in the patient satisfaction sub-scales score between the two groups (p>0.05). Conclusion: The present study demonstrates that PRP treatment is as satisfactory as conventional rehabilitation program in managing acute hamstring strain injury. Both modalities are correspondingly safe and have high degree of satisfaction. Given the acceptable outcomes, patients are likely to accept PRP as an effective treatment.